Anniversary souvenir 1961. [Amalgamated Union of Public Employees]. Forew. [by] Mak Kam Heng. [Contribs by] K.M. Byrne, Goh Keng Swee, [a.o.] (A.U.P.E., 1961)
Text in: English, Malayan, Indonesian, Chinese.